Roles of PIP2 in the membrane binding of MIM I‐BAR: insights from molecular dynamics simulations. Issue 15 (26th July 2018) - Lin, Xubo; Wang, Hongyin; Lou, Zhichao; Cao, Meng; Zhang, Zuoheng; Gu, Ning
Abstract : In order to probe the roles of PIP2 in the interactions between MIM I‐BAR and model membranes, we performed a series of 10 μs‐scale coarse‐grained molecular dynamics simulations. Our results indicate that PIP2 plays predominant roles in the membrane binding of MIM I‐BAR in a concentration‐dependent manner and via electrostatic interactions. Besides, we find that the occurrence of the membrane curvature may induce the re‐distribution of lipids in the membrane and result in the local enrichment of PIP2 at negatively curved membrane areas. Combining these roles of PIP2 in the membrane binding of MIM I‐BAR helps explain how MIM I‐BAR senses negative curvature and, thus, contributes to maintaining membrane protrusions. Abstract :